PARADIGMA WAKAF PRODUKTIF DALAM PRANATA HUKUM EKONOMI SYARIAH - Solihin, Dadin (Jurnal Pelita Nusa, 2022)
This research is motivated by the phenomenon of waqf where its implementation is more predominantly consumptive. The research focuses on the problems of juridical review, implementation, and hegemony of productive endowments in society. The goal is to be able to know the extent of the potential and efficiency of productive endowments to Mustahik. Qualitative descriptive research methods in the form of reviewing various scientific references in exploring the right theoretical perspective to understand the phenomenon under study. Where the results of the research found that the allocation of productively managed waqf assets is still minimal, the method of literacy, socialization, and inclusion of productive waqf needs to be massively conveyed to the public. In conclusion, regarding productive waqf, the Sharia paradigm and regulations in Indonesia are clear and tegs regulated, but the implementation dimension needs the involvement of all parties to create an equitable waqf allocation.